A contactless door lock controlled by portable devices. Issue 6 (1st August 2016) - Tu, Jih-Fu
Abstract : Purpose: – In our contemporary living environment, most people want, not only to maintain privacy and security, but also to avoid losing the keys or passwords for their doors at home. Additionally, many would like to own a fast, convenient and cost-effective exclusive door lock controller to establish some peace of mind. For this paper, the author has designed a smart door lock device which has a non-contact pattern recognition controller to recognize a tiny pattern that can be displayed by mobile devices. The paper aims to discuss this issue. Design/methodology/approach: – The patterns recognized by the exclusively designed security device are created using a two-dimensional text and graphics method that can be stored by mobile devices. Therefore, when key-owners come near their doors' control panels, the established two-dimensional text and graphics cyphers can be displayed for verification purposes on a mobile device's screen. The author used the MT19937 (32 bit) virtual random number generator as the encryption technology. Findings: – The recognized pattern is built using a two-dimensional text and graphics method that can be stored by owners' mobile devices. Therefore, when a key-owner comes near a door's control panel, the established two-dimensional text and graphics cypher can be displayed. Research limitations/implications: – Use of either wireless or wired internet causes momentary delays to lock control signals. Practical implications: – Upon each occasion of a code verification, doors are opened and short message service (SMS) notifications are sent to the key-owners simultaneously. The technology described in this paper can be used at any civilian installations that require door lock controls. The application range is very wide and can be customized readily. Social implications: – The technology discussed here could also be applied widely and easily in various fields. Originality/value: – The lock has a two-phase design for secure opening: i.e. mask-bit enabling and simultaneous SMS notification. The contactless smart door lock system combines three parts that are linked via the internet, which are a cloud server and database, a personal mobile device, and the device's fixtures and fittings. The fixtures and fittings include a complementary metal oxide silicon sensor, a limiting switch, an electromagnetic switch, a microcontroller unit, and an RJ-45 internet port. The results of this study could be applied at any civilian installation that requires door lock control.